Two-Dimensional Nanomaterials With Enzyme-Like Properties for Biomedical Applications - Cai, Shuangfei; Yang, Rong (Frontiers in Chemistry, 2020)
Recently, remarkable progress has been made in nanozyme research due to the rapid development of nanomaterials. Two-dimensional nanomaterials such as metal nanosheets, graphene-based materials, transition metal oxides/dichalcogenides, etc., provide enhanced physical and chemical functionality owing to their ultrathin structures, high surface-to-volume ratios, and surface charges. They have been also found to have high catalytic activities of natural enzymes such as peroxidase, oxidase, catalase, and superoxide dismutase. In this review, an overview of the recent progress of nanozymes based on two-dimensional nanomaterials is presented, with the emphasis on their synthetic strategies, hybridization, catalytic properties, and biomedical applications. Finally, the future challenges and prospects in this research area will be proposed.